Incidence of Diffuse Lamellar Keratitis After LASIK with 15 KHz, 30 KHz and 60 KHz IntraLase Femtosecond Laser Flap Creation - Choe, Christina H. (2010)
PURPOSE: To compare the incidence of diffuse lamellar keratitis (DLK) after laser in situ keratomileusis (LASIK) with flap creation using the IntraLase(®) 15 kHz (FS15), 30 kHz (FS30), or 60 kHz (FS60) femtosecond laser. SETTING: University-based academic practice, Ann Arbor, Michigan, USA METHODS: We retrospectively reviewed 520 consecutive myopic LASIK surgeries performed using the IntraLase FS15, FS30, or FS60 femtosecond laser for flap creation from January 1, 2005 to June 1, 2007. Preoperative clinical characteristics, treatment parameters, intraoperative and postoperative complications were recorded. Statistical comparisons were made using repeated measures analysis, analysis of variance, chi-square, and Fisher’s exact tests. RESULTS: Five hundred twenty eyes of 274 patients were included in the study. One hundred seventy-six eyes (93 patients) were treated using the FS15 laser, 180 eyes (93 patients) with the FS30 laser, and 164 eyes (89 patients) with the FS60 laser. Seventeen eyes (10%) in the FS15 laser group, 24 eyes (13%) in the FS30 laser group, and 23 eyes (14%) in the FS60 laser group developed DLK. There was no statistically significant difference in the incidence of DLK among the three groups (p=0.68). CONCLUSION: This study found no significant difference in the incidence of DLK among the FS15, FS30, and FS60 groups.